Efisiensi Operasional Dengan Adanya Rapid Exit Taxiway Dan Parallel Taxiway Di Bandara-Bandara Di Indonesia - Rahman, Cahaya Purnama; Septian, Marheindranata; Pancasakti, Tigor; Ananda, Vika (Publikasi Indonesia, 2025)
The growth of air transportation passengers exceeds the growth of existing facilities and infrastructure at the airport, so problems related to services will arise, both on the ground side and on the air side. Knowing airport capacity plays an important role in airport planning, this is one of the disciplines in airport management. One of the common obstacles faced in flight operations at domestic airports in Indonesia is that planes are required to wait at the edge of the runway (hold-short) for a few minutes because other planes will land. Another situation is when two aircraft with close departure times have to wait for the first aircraft to turn around on the runway (enter back-track runway) and take off before the second aircraft is allowed by ATC to perform the same maneuver because the taxiway to the runway is positioned in the middle. In addition to the absence of parallel taxiways at many airports in Indonesia, another problem that can arise when air traffic increases is the long queues because the distance between arrivals/departures of planes cannot be optimized. This condition occurs due to the absence of a rapid exit taxiway so that the landing plane takes longer to deceliate and exit the runway. As air traffic grows, planning the construction of parallel taxiways and rapid exit taxiways at domestic airports in Indonesia will reduce the waiting time between aircraft arrivals/departures and increase efficiency in flight operations.